The efficiency of long primers compared to the short primer for RAPD technique in date palm / Aisyah Mohd Ismail and Farida Zuraina Mohd - Mohd Ismail, Aisyah; Mohd, Farida Zuraina (Universiti Teknologi MARA, 2022)
Random Amplified Polymorphic DNA (RAPD) applies single arbitrary short primers (8-12 nucleotides) to produce many amplified discrete DNA. Limited reports and studies were done on the use of long primers (over 12 bases). This study was performed to investigate the potential value of long primers (15-21 bases) for generating RAPD polymorphisms. We compared both short and long primers in RAPD assays of two date palm cultivars grown in Malaysia: Ajwa and Barhi. The number of produced polymorphic fragments ranged in order from 2 and 38 bands for short and long primers in Ajwa. Meanwhile, more polymorphic fragments were generated by long primers in Barhi, which were 50 and only five bands for short primers. 18-mer GY107 and 20-mer CO4 primers yielded 100% polymorphism in Ajwa and Barhi, respectively. Moreover, long primers produced more DNA fragments and a wider range of DNA fragment sizes (from 140-1600 bp, with respect to 300-1000 bp obtained with 10-mer primers). Hence, a significant correlation was observed between primer length and the number of polymorphic fragments within the long primer group, suggesting that increasing primer length above 15 bases may demonstrate enhanced production of more polymorphism.